2020
DOI: 10.3758/s13414-020-02085-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel, unbiased approach to evaluating subsequent search misses in dual target visual search

Abstract: Research in radiology and visual cognition suggest that finding one target during visual search may result in increased misses for a second target, an effect known as subsequent search misses (SSM). Here, we demonstrate that the common method of calculating second-target detection performance is biased and could produce spurious SSM effects. We describe the source of that bias and document factors that influence its magnitude. We use a modification of signal-detection theory to develop a novel, unbiased method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In the current study, there was no significant difference in dual-target accuracy (defined as the percentage of dual-target trials where both targets where found) between groups (low-expectation: mean = 56.16%, SD = 14.23%, high-expectation: mean = 53.09%, SD = 18.76%; t (82) = − 0.84; p = 0.41) and a Bayes factor analysis found substantial evidence in favor of the null hypothesis ( B 01 = 4.31). However, measuring the SSM effect involves specifically comparing accuracy for a second-target to a single-target accuracy baseline (a number of different metrics have recently been proposed for measuring the SSM effect, see Adamo et al, 2019 ; Becker et al, 2020 ). Therefore, despite the lack of a significant difference in dual-target accuracy, there was a significant difference in the measures of the SSM effect between groups using all of the metrics from both Adamo et al, 2019 and Becker et al 2020 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, there was no significant difference in dual-target accuracy (defined as the percentage of dual-target trials where both targets where found) between groups (low-expectation: mean = 56.16%, SD = 14.23%, high-expectation: mean = 53.09%, SD = 18.76%; t (82) = − 0.84; p = 0.41) and a Bayes factor analysis found substantial evidence in favor of the null hypothesis ( B 01 = 4.31). However, measuring the SSM effect involves specifically comparing accuracy for a second-target to a single-target accuracy baseline (a number of different metrics have recently been proposed for measuring the SSM effect, see Adamo et al, 2019 ; Becker et al, 2020 ). Therefore, despite the lack of a significant difference in dual-target accuracy, there was a significant difference in the measures of the SSM effect between groups using all of the metrics from both Adamo et al, 2019 and Becker et al 2020 .…”
Section: Resultsmentioning
confidence: 99%
“…However, measuring the SSM effect involves specifically comparing accuracy for a second-target to a single-target accuracy baseline (a number of different metrics have recently been proposed for measuring the SSM effect, see Adamo et al, 2019 ; Becker et al, 2020 ). Therefore, despite the lack of a significant difference in dual-target accuracy, there was a significant difference in the measures of the SSM effect between groups using all of the metrics from both Adamo et al, 2019 and Becker et al 2020 . Critically, these differences were driven by the difference in the single-target baseline, so reffering to them as true differences in the SSM effect is complicated (see discussion).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Becker et al ( 2020 ) argued the above approach is limited by its restrictive experimental design (i.e., that using matched displays can limit the number of dual-target trials within an experiment as there has to be two matched single-target trials). Furthermore, they hypothesized that stimulus matching is an imperfect correction for biases caused by differences in second-target detection difficulty and argued that biases could exist beyond those induced by stimulus display properties.…”
Section: Ssm Methods and Calculationsmentioning
confidence: 99%
“…Becker et al ( 2020 ) demonstrated that by using this equation on the data reported in Adamo et al ( 2019 ) (which is based on the same displays and targets used in many prior SSM studies; e.g., Adamo et al, 2013 , 2017 , 2018 ; Cain & Mitroff, 2013 ), this approach results in a smaller, but still significant, SSM effect compared to both the non-matched and matched search display design/data tested in Adamo et al ( 2019 ) (see Becker et al, 2020 and Table 2 below for examples of how the SSM effect sizes change with different calculation methods).…”
Section: Ssm Methods and Calculationsmentioning
confidence: 99%